Acute Peritoneal Dialysis in the Newborn Period: A 7-Year Single-Center Experience at Tertiary Neonatal Intensive Care Unit in Turkey - Hakan, Nilay; Aydin, Mustafa; Zenciroglu, Aysegul; Aydog, Ozlem; Erdogan, Derya; Karagol, Belma Saygili; Dursun, Arzu; Okumus, Nurullah (American Journal of Perinatology, 2014)
Objective To evaluate the underlying causes and outcomes of neonates who underwent acute peritoneal dialysis (APD).Study Design This report describes a 7-year experience with APD in 77 neonates.Results Underlying causes requiring APD were acute tubular necrosis (ATN; n = 53), inborn error of metabolism (n = 18), bilateral renal vein thrombosis (n = 3), obstructive uropathy (n = 2; posterior urethral valve and neurogenic bladder), and bilateral renal artery thrombosis (n = 1). Fifteen of the 53 patients developed post–cardiac surgery ATN. The mean dialysis duration was 6.2 ± 10.7 days (range 1 to 90 days). Complications of procedure were hyperglycemia (n = 35), leaking of dialysate (n = 13), peritonitis (n = 10), catheter obstruction (n = 3), bleeding when inserting the catheter (n = 3), exit site infection (n = 2), and bowel perforation (n = 1). There were 57 deaths (74%) in this high-risk group due to underling causes. Of the 20 survivors, 16 patients showed a full renal recovery, but mild chronic renal failure developed in 1 patient and proteinuria with/without hypertension in 3 patients.Conclusion Peritoneal dialysis is an effective means of renal replacement therapy in the neonatal period in the management of metabolic disturbances as well as renal failure. Although major complications of procedure are not so common, these patients have high mortality rates due to the serious nature of the primary causes.
Keywords: acute renal failure; hyperammonemia; metabolic disorders; acute peritoneal dialysis; newborn; neonatal intensive care unit; complication; mortality